If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.2x + -2.7 = 3.6x + 2.6 Reorder the terms: -2.7 + 0.2x = 3.6x + 2.6 Reorder the terms: -2.7 + 0.2x = 2.6 + 3.6x Solving -2.7 + 0.2x = 2.6 + 3.6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.6x' to each side of the equation. -2.7 + 0.2x + -3.6x = 2.6 + 3.6x + -3.6x Combine like terms: 0.2x + -3.6x = -3.4x -2.7 + -3.4x = 2.6 + 3.6x + -3.6x Combine like terms: 3.6x + -3.6x = 0.0 -2.7 + -3.4x = 2.6 + 0.0 -2.7 + -3.4x = 2.6 Add '2.7' to each side of the equation. -2.7 + 2.7 + -3.4x = 2.6 + 2.7 Combine like terms: -2.7 + 2.7 = 0.0 0.0 + -3.4x = 2.6 + 2.7 -3.4x = 2.6 + 2.7 Combine like terms: 2.6 + 2.7 = 5.3 -3.4x = 5.3 Divide each side by '-3.4'. x = -1.558823529 Simplifying x = -1.558823529
| 4(z+3)-7z= | | 4(6x)=20 | | 63=-8n-5(5n-6) | | h=-16t^2+120t+4 | | 2.5=30x | | 5.32*(10-y)+3.6y=79 | | 1/9x3/4 | | 2x/15+4=71/5 | | 16+3x=-8 | | 7x=(2x-71)/23 | | -3(-7x-1)=45 | | 0.23-0.03(x+3)=-0.01(2-x) | | 5.3*(10-y)+3.6y=79 | | -8r+2(1+8r)=-62 | | -27=5(1+7m)-3m | | 3(z+4)-6z= | | (x/40)+(x/60)=1 | | 5b=13a+5 | | 7/2a=35 | | 4/7x1/7 | | 45=5(n+1) | | -7x^2-x+5=0 | | 2(8k+9)= | | -7=-4x+3(x-4) | | 12+5(6-7)=2 | | 3/8u=-15 | | 58+5x=3 | | h=-16t^2+100+3 | | 0.08-0.02(x+2)=0.02(2-x) | | 25*1.05-0.05(25*1.05)=25 | | 2y-3x=15 | | 3/8u=-35 |